THE USE OF ICT IN THE DIDACTIC PROCESS OF STUDENTS' EDUCATION - Cupial, Michal; Szeląg-Sikora, Anna; Kuboń, Maciej (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The modern education process requires introduction of modern information and communication technologies (ICT) in order to make classes more attractive, to properly implement curricular content and, as a consequence, to provide students with education compliant with applicable standards. Some didactic classes are more predisposed to the use of ICT, and others to a lesser extent. The Faculty of Production and Power Engineering of the University of Agriculture in Krakow has been using modern IT solutions to support the teaching process for many years. The mentioned ICT tools include the e-learning platform Moodle, office packages (Microsoft Office, Open Office), groupware tools, Internet platform Google Apps, Microsoft IT Academy and many specialized software. This study presents a case study of the use of ICT tools during selected subjects at the faculty.